PENINGKATAN RESPONSE DAN LOAD TIME DALAM MENAMPILKAN CITRA SATELIT PENGINDERAAN JAUH PADA APLIKASI WEB GIS SISTEM PEMANTAUAN BUMI PROVINSI - Jusuf, Rubini; Yudha, Gusti Darma; Oktavia, Masnita Indriani; Siwi, Sukentyas Estuti; Hutapea, Destriyanti; Purnama, Syaiful Muflichin; Rizkiyanto, Rahmat (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2018)
Provincial based Earth Monitoring System (SPBP) LAPAN is provided to meet the needs of local governments related to the management and distribution of geospatial information data in the form of remote sensing data and thematic geospatial data. GIS (Geographic Information System) mapping through Web or called Web GIS is one way to display and distribute maps online. Web GIS is built to provide convenience and speed of access by users. Web Map Service (WMS) data access speed method on the SPBP system is considered quite slow along with increasing the volume of data processed. This research aims to improve the performance of the Web GIS in response to user requests and speed in displaying image (load time) Landsat-8 and SPOT-6/7 mosaics. The object of this research is remote sensing satellite image in Kepulauan Riau Province. Performance tests are carried out with comparing several sizes of tile maps with the Web Map Tile Service (WMTS) method and manual tiling as a solution to replace the WMS system. Measurements on system request for use on both WMTS and manual tiling showed a not significant difference. But the WMTS tile map is much faster in displaying mosaic data which reaches an average number of less than 3 seconds. Base on the results of this study the Web GIS with the WMTS method is the basis of SPBP development, in order to optimize the speed of access of Landsat-8 and SPOT-6/7 mosaic image data.